Factors Affecting Audit Report Lag (Empirical Studies on Manufacturing Listed Companies on the Indonesia Stock Exchange) - Jura, Jacqueline Vania Jessica; Tewu, ML Denny (Petra International Journal of Business Studies, 2021)
The objective of this research is to determine whether Company Size, Company Age, Debt to Equity (DER), Return on Assets (ROA), Audit Opinion, and Auditor Reputation have a significant effect on Audit Report Lag. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the period 2015 to 2019. The study used 93 companies as samples, a total of 490 samples as a whole. The data analysis technique used is multiple linear analysis and the results obtained are that the DER variable has a significant positive effect, while ROA and Audit Opinion have a negative effect on the audit report lag. The variables of company size and auditor reputation do not have a significant effect, while the variable of company age has a significant positive result but is contrary to the initial expectations.